Reviews. - SHERR, BARRY; SLOBIN, GRETA; HUDSPITH, SARAH; ROBERTS, GRAHAM H.; ULRICH, JOHN M.; CHITNIS, RAJENDRA A.; RUTHCHILD, ROCHELLE G.; SPERLING, VALERIE; FAIRCLOUGH, PAULINE; MEDIC, IVANA; PETEK, POLONA; MIAZHEVICH, GALINA; et al. (Slavonica, 2008)
The article reviews several books including "The Poetry of Prose: Readings in Russian Literature," by Jostein Bøstnes, "The Dedalus Book of Russian Decadence: Perversity, Despair and Collapse," edited by Kirsten Lodge, and "Reawakening National Identity: Dostoevskii's Diary of a Writer and its Impact on Russian Society," by Raffaela Vassena.